A study of vitamin D supplementation with directly observed treatment short course for Pulmonary Tuberculosis - Randhawa, Gurpreet Kaur; Jindal, Suneet; Rai, Jaswant; Kajal, Nirmal Chand (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Tuberculosis remains one of major global health problems due to growing resistance in TB bacilli against anti-tubercular treatment (ATT). Vitamin D3 has been reported to have immunostimulatory effect. Aim was to study effect of Vitamin D3 on efficacy and safety of ATT / Directly Observed Treatment, short course regimen. Methods: Prospective, randomized and interventional study of 90 days was carried out in 60 newly diagnosed sputum positive pulmonary tuberculosis patients on DOTS strategy. Study was conducted in Government Medical College, Amritsar, Punjab, India. 30 patients each were randomly divided into two groups, A and B, with group A - vitamin D3 and DOTS regimen and Group B - DOTS alone. Patients were evaluated on day 0, 30, 60 and 90 by TB score, sputum microscopy, laboratory investigations, and adverse drug events. At the end of 90 days, results were tabulated and data analyzed statistically applying relevant tests. Results: Statistically non-significant improvement in symptoms, sputum conversion and decrease in mean TB scores was seen in Group A vs B at 90 days. Significant increase in mean Vitamin D levels was seen in Group A at end of study. Insignificant difference in safety profile was observed in group A which showed additional adverse events suspected to be due to Vitamin D. Equivocal hepatoprotective effect of Vitamin D was observed. Conclusions: Vitamin D as adjuvant to ATT does not confer additional benefit to newly diagnosed pulmonary tuberculosis patients. Large multi-centric trials are required to find any benefit of Vitamin D supplementation with ATT.